ACTUALIZATION OF STUDENT’S SOCIAL RESPONSIBILITY IN EFFORTS TO STRENGTHEN CIVIC ENGAGEMENT (Case Study at Student Association of Civic Education in Faculty of Teachers Training and Education, Lambung Mangkurat University) - Wardiani Hiliadi , Suwarma Al Muchtar (Institut Agama Islam Ngawi, 2017)
ABSTRACT; This study examines the value development of social responsibility owned by the students of civic education, Faculty of Teacher Training and Education (FKIP) in University of Lambung Mangkurat, as an effort of social engagement of students in the form of social service as one of the work programs of the Civic Education Student Association, University of Lambung Mangkurat. The aims of this study, among others; 1) Assess the social work activities of